Biofunctionalization of hydrogel-based scaffolds for vascular tissue regeneration - López-Gutierrez, Jorge; Ramos-Payán, Rosalío; Ayala-Ham, Alfredo; Romero-Quintana, José Geovanni; Castillo-Ureta, Hipolito; Villegas-Mercado, Carlos; Bermúdez, Mercedes; Sanchez-Schmitz, Guzman; Aguilar-Medina, Maribel (Frontiers in Materials, 2023)
Congenital and acquired tissular losses due to disease or trauma are a major world health problem. Regenerative therapy aims to fix damaged tissues by directing the natural capacity of a host organism to use biofunctionalized artificial tissue scaffolds. These three-dimensional (3D) scaffolds can be customized with cells and/or bioactive molecules to induce cellular homing and angiogenesis, essential to ensure successful tissue regeneration. Hydrogels (HGs) scaffolds are networks of hydrophilic homopolymers, copolymers, and/or macromers with chemical and biological activities that enhance their cell colonization. The use of HGs in regenerative medicine has shown to be advantageous since HGs can be prepared under clinical-grade conditions and tailored to the specific needs of the replaced tissue. They can be made to emulate native extracellular matrices (ECMs) including physical, mechanical, and chemical cues and resilience properties. These customized HGs can reproduce the natural hygroscopic capacity of the original tissue which improves cellular anchoring, nutrition, and waste disposal. They can enable host molecular and cellular modification conducive to a natural cellular microenvironment, modifying the properties of the scaffold, and improving chemotaxis, cell adhesion, migration, proliferation, differentiation, and angiogenesis; HGs can be created and biofunctionalized with linked growth factors and synthetic peptides tailored to positively influence scaffold colonization and functional biocompatibility. This review aims to collect the most relevant information regarding biofunctionalization of HGs used for vascular tissue regeneration, their biological effects, and their clinical implications. While most biofunctionalized HGs are still under investigation, some of them have been studied in vitro, ex vivo, and in vivo with promising results. In this regard, in vivo studies have shown that biofunctionalized scaffolds with peptides such as chitosan hydrogel with LL-37 promotes angiogenesis and healing of pressure ulcers. Also, the GHK tripeptide is widely used in trials focused on guided tissue remodeling.